Financial Hardship, Motivation to Quit and Post-Quit Spending Plans among Low-Income Smokers Enrolled in a Smoking Cessation Trial. (October 2019) - Rogers, Erin; Palacios, Jose; Vargas, Elizabeth; Wysota, Christina; Rosen, Marc; Kyanko, Kelly; Elbel, Brian D.; Sherman, Scott
Background: Tobacco spending may exacerbate financial hardship in low-income populations by using funds that could go toward essentials. This study examined post-quit spending plans among low-income smokers and whether financial hardship was positively associated with motivation to quit in the sample. Methods: We analyzed data from the baseline survey of a randomized controlled trial testing novel a smoking cessation intervention for low-income smokers in New York City ( N = 410). Linear regression was used to examine the relationship between financial distress, food insecurity, smoking-induced deprivation (SID) and motivation to quit (measured on a 0-10 scale). We performed summative content analyses of open-ended survey questions to identify the most common plans among participants with and without SID for how to use their tobacco money after quitting. Results: Participants had an average level of motivation to quit of 7.7 ( SD = 2.5). Motivation to quit was not significantly related to having high financial distress or food insecurity ( P > .05), but participants reporting SID had significantly lower levels of motivation to quit than those without SID ( M = 7.4 versus 7.9, P = .04). Overall, participants expressed an interest in three main types of spending for after they quit: Purchases, Activities, and Savings/Investing, which could be further conceptualized as spending on Oneself or Family, and on Needs or Rewards. The top three spending plans among participants with and without SID were travel, clothing and savings. There were three needs-based spending plans unique to a small number of participants with SID: housing, health care and education. Conclusions: Financial distress and food insecurity did not enhance overall motivation to quit, while smokers with SID were less motivated to quit. Most low-income smokers, including those with SID, did not plan to use their tobacco money on household essentials after quitting.